Influenza like illness (ILI) outbreak in Kulon Progo District, Yogyakarta – November 2019 - Meutia Fildzah Sharfina (BKM Public Health and Community Medicine, 2021)
Objective: The case started with 10 students in one of Kulon Progo District junior high school, Yogyakarta who felt sick on November, 20th 2019 morning. The total cases up to school hours increased to 30 students. Epidemiology investigation was held to find other additional cases. Method: This research was using descriptive study design. The case definition in this outbreak is a student in one of Kulon Progo District junior high schools who felt one of ILI clinical symptoms such as headache, shortness of breath, muscle aches, diarrhea, nausea or vomiting November, 3rd 2019 until December, 8th 2019. Clinical symptoms of ILI are fever, cough, cold, muscle aches, or sore throat. The data were collected using questionnaires filled out by the students. Results: The ILI epidemiological curve has shown one peak or common source. The highest case was found on November, 19-20th 2019 with 70 cases. Total population at risk is 392 students and 159 of them are ill. The Attack Rate (AR) in this outbreak is 40.56%. The case distribution was 50,94% for male and 49.06% for female. The most cases which occurred in students was at the age of 14 years (47.24%). The dominant symptoms were headache (35.71%), cough (32.40%), and fever (26.53%). An identifiable risk factor of the ILI outbreak is contact with other ILI cases. Based on the results of the questionnaire, 24.53% of cases of direct contact with family members who had a history of illness with ILI symptoms. Conclusion: An ILI outbreak occurred at one of the junior high schools in Kulon Progo District from November, 3rd until December, 8th 2019. Local health authorities should improve the early detection system of ILI outbreak by improving cooperation between health officials and local health cadres.